2013
DOI: 10.1186/1748-5908-8-138
|View full text |Cite
|
Sign up to set email alerts
|

Organizational readiness for knowledge translation in chronic care: a review of theoretical components

Abstract: BackgroundWith the persistent gaps between research and practice in healthcare systems, knowledge translation (KT) has gained significance and importance. Also, in most industrialized countries, there is an increasing emphasis on managing chronic health conditions with the best available evidence. Yet, organizations aiming to improve chronic care (CC) require an adequate level of organizational readiness (OR) for KT.Objectives: The purpose of this study is to review and synthesize the existing evidence on conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…As for Shaw et al [23], they found that change was facilitated because the program aligned with the values and goals of the organization. To conclude this section on contextual factors, the findings of Attieh et al [14] summarizes well the state of knowledge on their importance, to the effect that they influence readiness and are considered a key dimension in the assessment of ORC.…”
Section: Contextual Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…As for Shaw et al [23], they found that change was facilitated because the program aligned with the values and goals of the organization. To conclude this section on contextual factors, the findings of Attieh et al [14] summarizes well the state of knowledge on their importance, to the effect that they influence readiness and are considered a key dimension in the assessment of ORC.…”
Section: Contextual Factorsmentioning
confidence: 98%
“…After conducting a systematic review of literature Attieh et al [14] synthesized the existing evidence on conceptual models/ frameworks of ORC in healthcare services and used these as a basis to develop a comprehensive framework of ORC. As a result of their work, these authors conclude that researchers give varied definitions to concepts related to the ORC.…”
Section: Orc Definitionmentioning
confidence: 99%
“…This paper develops that analysis by highlighting how healthcare managers' priorities, challenges and expectations, impact on health system capability for transformation [7,8].…”
Section: Methodology Conceptual Frameworkmentioning
confidence: 99%
“…In an extensive review of 106 peer-reviewed articles on organizational readiness for change, Weiner et al [18] concluded that the content of a comprehensive organizational readiness tool should include a psychological and structural approach at an individual and organizational level that respects both macro-level structural factors and micro-level factors (e.g., individual differences). Recently, Attieh et al’s [19] review of organizational readiness for knowledge translation in chronic care identified five core concepts, namely: organizational dynamics, change process, innovation readiness, institutional readiness and personal readiness.…”
Section: Introductionmentioning
confidence: 99%